Comprehensive investigation of ergonomic challenges and predictors of work-related musculoskeletal disorders among intensive care unit nurses of Western India through convergent mixed methods study - Sonali Detroja; Rajkumar Mahajan; Ankit Sheth (BMC Musculoskeletal Disorders)
Abstract Background Work-related musculoskeletal disorders (WRMSDs) are significant concern in intensive care units (ICUs) due to distinct work environment. This study aims to comprehensively investigate determinants of WRMSDs and ergonomic challenges, specific to ICU nurses, providing valuable insights for targeted interventions. Methods In this six-month convergent mixed methods study, 200 consenting nurses with over one year of experience from seven ICUs across three public tertiary hospitals of Ahmedabad participated. Structured questionnaires were used to collect data on socio-demographics, occupation, physical and workplace factors, risk perception, and musculoskeletal pain (through modified Nordic Musculoskeletal Questionnaire) and ergonomic issues using REBA (Rapid Entire Body Assessment) scale. Qualitative insights were obtained through in-depth interviews until saturation of responses. Statistical analysis involved chi-square, t-test and logistic regression, with a significance level set at p < 0.05. Thematic analysis was used to interpret the findings of qualitative study. Results The study included predominantly female ICU nurses (78%) with a mean age of 34 years. A high prevalence of WRMSDs (84%) was observed, with the lower back and neck being the most affected regions. Nurses with WRMSDs reported significantly higher mean scores for physical factors (15.1 vs. 11.1, p = 0.00), physical workload (12.8 vs. 10.7, p = 0.001), work environment (13.1 vs. 10.1, p = 0.00), and risk perception (11.8 vs. 8.9, p = 0.00) compared to those without WRMSDs. Logistic regression identified key risk factors for WRMSDs, including longer ICU tenure [OR = 1.4 (1.13–1.66)], high shift frequency [OR = 2.7 (1.27–5.95)], higher physical factor score [OR = 1.2 (1.05–1.42)], higher physical workload score [OR = 1.2 (1.09–1.49)], higher risk perception [OR = 1.3 (1.10–1.78)], and lack of exercise [OR = 0.5 (0.27–0.93)]. The qualitative findings highlighted key ergonomic challenges, including inadequate equipment, heavy patient loads, poor posture during tasks, and insufficient breaks, contributing to WRMSDs among ICU nurses. Conclusion The findings underscore urgent need for targeted interventions to address risk factors associated with WRMSDs, including ergonomic training, workplace modifications, and education programs to enhance risk awareness and preventive behaviours. Future research should focus on developing and evaluating comprehensive interventions that integrate both physical and work environment factors to effectively mitigate WRMSDs among ICU nurses.